OPTIMIZATION OF TECHNOLOGICAL PROCESSES FOR THE MECHANICAL MACHINING OF INTERNAL CYLINDRICAL SURFACES OF VARIOUS DIMENSIONS (Web of Discoveries: Journal of Analysis and Inventions, 2025)
Internal cylindrical surfaces are among the most critical geometries in mechanical components, especially in the automotive, aerospace, and hydraulic industries. Achieving high dimensional accuracy and surface quality in the machining of these surfaces is essential to ensure proper functionality and longevity of assemblies. However, machining bores of different diameters presents significant challenges, including chip removal difficulties, tool vibration, thermal deformation, and varying cutting force distribution.